The Influence of Metal Loading Amount on Ni/Mesoporous Silica Extracted from Lapindo Mud Templated by CTAB for Conversion of Waste Cooking Oil into Biofuel - Cahyarani Paramesti; Wega Trisunaryanti; Savitri Larasati; Nugroho Raka Santoso; Sri Sudiono; Triyono Triyono; Dyah Ayu Fatmawati (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
The synthesis and characterization of Ni/mesoporous silica (Ni/MS) catalysts from Lapindo mud with various metal loading for the hydrocracking of waste cooking oil into biofuel has been conducted. The MS was synthesized by the hydrothermal method using CTAB as a template. The nickel-metal of 4, 6, and 8 wt% was loaded into the MS using salt precursors of Ni(NO3)2.6H2O via wet impregnation, produced the Ni(4)/MS, Ni(6)/MS, and Ni(8)/MS catalysts, respectively. The materials produced were then characterized by X-ray Powder Diffraction (XRD), Fourier-Transform Infrared Spectroscopy (FT-IR), and Surface Area Analyzer (SAA), and Absorption Atomic Spectrophotometry (AAS). The catalytic activity test was carried out for hydrocracking of waste cooking oil and the resulted liquid product was analyzed by Gas Chromatography-Mass Spectrometry (GC-MS). The results showed that the specific surface area of Ni(4)/MS, Ni(6)/MS, and Ni(8)/MS catalysts are 63.08, 91.45, and 120.45 m2/g, respectively. The liquid products of the hydrocracking using Ni(4)/MS, Ni(6)/MS, and Ni(8)/MS catalysts were 80.57, 74.63, and 75.77 wt%, where the total biofuel produced was 55.46, 50.93, and 54.05 wt%, respectively. Based on these results, Ni(4)/MS material was successfully used as the most potent catalyst in the hydrocracking of waste cooking oil into the biofuel. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).